Histodynamics of calcium phosphate coating on the osseointegration of medical-grade polycaprolactone β-tricalcium phosphate scaffolds - Medeiros Savi, Flavia (Frontiers in Biomaterials Science, 2024)
Bone formation on implant surfaces occurs via distance and contact osteogenesis, with osseointegration influenced by the implant's surface topography and coating. However, the traditional mechanisms of osseointegration around metal implant surfaces may not fully encompass the ultimate outcomes of using medical-grade polycaprolactone β-tricalcium phosphate calcium phosphate coated (mPCL-TCP-CaP) scaffolds for the reconstruction of large bone defects. Our studies on large bone defects using mPCL-TCP-CaP scaffolds show osteogenic cells forming a collagenous fibrous connective matrix around these scaffolds. Despite extensive research, the in vivo mechanisms of osseointegration of CaP-coated mPCL-TCP-CaP scaffolds remain unclear. This study investigates the structural details and spatial organization of the mPCL-TCP-CaP scaffold's interface, providing insights into the histodynamic processes involved in their osseointegration with CaP coatings.